2013
DOI: 10.1039/c3ob40657a
|View full text |Cite
|
Sign up to set email alerts
|

CuI-catalyzed and air promoted oxidative cyclization for one-pot synthesis of polyarylated oxazoles

Abstract: A facile CuI-catalyzed and air promoted oxidative cyclization was developed for the synthesis of polyarylated oxazoles. By virtue of this method, a variety of arylated oxazoles could be easily synthesized from readily available starting materials at room temperature in air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…At first, Benzoin ( 1 b ) is oxidized to benzil in presence of iodine . Initially, diketone Breacted with the corresponding amine to produce the addition product C ,. Next, K 2 CO 3 promoted iodination of C gives iodine intermediate E via D andliberate HI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At first, Benzoin ( 1 b ) is oxidized to benzil in presence of iodine . Initially, diketone Breacted with the corresponding amine to produce the addition product C ,. Next, K 2 CO 3 promoted iodination of C gives iodine intermediate E via D andliberate HI.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently easily accessible 1,2‐diketone (benzil) were exploited for the synthesis of fully substituted oxazole, (Scheme ). Regardless of their applicability and broad substrate scope, these methods suffer from limitations of transition metal reagent and organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction condition is mild and moderate to good yields could be obtained at room temperature. The C(sp 3 )-H bond of benzylamine was activated in this transformation [116]. Jiao et al reported the synthesis of oxazoles from aldehydes, amines, and molecular oxygen through a CuBr 2 -mediated aerobic oxidative dehydrogenative annulation [117].…”
Section: Copper-catalyzed Synthesis Of Pyrazoles and Indazolesmentioning
confidence: 99%
“…11b Another copper mediated domino process by Wang's group leading to polyarylated oxazoles was also attractive, but a minor limitation was that the protocol cannot be applied in the construction of 2-pyridyl substituted oxazoless ( Figure 2, eq 4). 12 It is obvious that extra oxidants or heavy metals were necessary to promote the reactions in the above mentioned reactions. The reason why it is worthy to synthesize oxazoles with an effective means is that tedious synthetic procedures and purification are obstacles of the application of oxazoles.…”
Section: Introductionmentioning
confidence: 99%